ECONOMIC DEVELOPMENT OF THE USSR AND GERMANY IN THE 1930s – EARLY 1940s (Political and economic aspects) - Ivan V. Popov (Plekhanov Russian University of Economics, 2017)
The recent attempts made by some experts to show the USSR and German Nazi Reich as similar totalitarian regimes usually were based on certain ideological and economic stereotypes. Biased character and political engagement of such an approach become evident during serious analysis of the initial material. The authors assess the legitimate nature of using the definition ‘totalitarian regime’ applied to the USSR and Germany before the World War 2. The article provides a comparative analysis of processes of economic modernization, structural changes in production complexes in the two countries. The authors acknowledged some elements of formal similarity in their economic development but they pointed out to drastic differences both in ideology and goals of economic reforms carried out during the mentioned period by authoritarian political regimes of the two countries.